Legitimation of the Referendum - The Standard Mechanism of Participatory Democracy (Journal of Legal Studies, 2017)
The referendum is a multidimensional instrument, attested and practiced worldwide, considered to be a compulsory feature of democracy, provided it is used under strict lawfulness. The purpose of putting it into practice is to know the sovereign will of the people, expressed by vote, on a particular issue subject to its decision-making capacity. Following the referendum process, and in the case of referendum forms, such as the legislative or decision-making process, the referendum generates the obligation for the governing authorities to implement the decision adopted by the people. It is certain that the people's response to the referendum question materializes a decision that emanates from the people, and which benefits in this way of increased legitimacy. Legitimacy is a concept that unleashes the force of the referendum, the result of which is imposed on everyone, the minority who voted against, and the governors. Legitimacy gives an institutional sense to the referendum, being an immanent part of the entire referendum process. It comes from the principle of the sovereign will of the people, which once expressed, is imposed on all the executive factors that must apply it. Legitimacy is both an intrinsic quality of the referendum and its effect, as it gives force to the outcome and justifies any political, legislative or administrative action or inaction. If the referendum process were deprived of legitimacy, or the resulting decision would be denied of this supreme attribute, then the referendum would be an artificial institution, empty of content, virtually useless.